Understanding Mission Today: Points of Convergence?. (October 2017) - Ross, Kenneth R
In this brief article, essential content from mission statements by three different church groupings is compared and contrasted. Lausanne's Cape Town Commitment is brought together with the WCC's Together Towards Life and the Vatican's Evangelii Gaudium. This article identifies considerable convergences between the three agendas and sees these as grounds not only for general optimism for the future of mission, but also for meaningful dialogue and appropriate strategies for the work.